1985
DOI: 10.1128/jb.163.2.778-782.1985
|View full text |Cite
|
Sign up to set email alerts
|

Succinate dehydrogenase in Rhodopseudomonas sphaeroides: subunit composition and immunocross-reactivity with other related bacteria

Abstract: Antibodies were raised against the succinate dehydrogenase (SDH) present in the chromatophores of phototrophically grown Rhodopseudomonas sphaeroides. Crossed immunoelectrophoresis experiments indicated that the SDH present in the cytoplasmic membranes of heterotrophically grown R. sphaeroides is probably the same enzyme observed in the chromatophores. The enzyme was extracted by Triton X-100 in a form which consisted of only two subunits (molecular weight, 68,000 and 30,000) and was not associated with a cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…This result agrees with previous reports which showed that Sdh is located in the chromatophores of phototrophically grown R. sphaeroides. 66 Recently, Zeng et al have found that two subunits of the succinate dehydrogenase are also found in the ICM. 31 This finding corroborates previous studies which showed that some respiratory electron carriers were present in the ICM, either due to their role in the bioenergetic light reactions of photosynthesis or in the control of expression of the photosynthetic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with previous reports which showed that Sdh is located in the chromatophores of phototrophically grown R. sphaeroides. 66 Recently, Zeng et al have found that two subunits of the succinate dehydrogenase are also found in the ICM. 31 This finding corroborates previous studies which showed that some respiratory electron carriers were present in the ICM, either due to their role in the bioenergetic light reactions of photosynthesis or in the control of expression of the photosynthetic apparatus.…”
Section: Discussionmentioning
confidence: 99%